3-D tissue-engineered epidermis against human primary keratinocytes apoptosis via relieving mitochondrial oxidative stress in wound healing - Shan He; Han Wu; Junqun Huang; Qingyan Li; Zijie Huang; Huangding Wen; Zhiqing Li (Journal of Tissue Engineering, 2023)
The tissue-engineered epidermal (TEE), composed of biocompatible vectors and autogenous functional cells, is a novel strategy to solve the problem of shortage of donor skin sources. The human primary keratinocyte (HPK), the major skin components, are self-evident vital in wound healing and was considered as one of the preferred seed cells for TEEs. Since the process of separating HPKs from the skin triggers a stress state of the cells, achieving its rapid adhesion and proliferation on biomaterials remains challenging. The key to the clinical application is to ensure the normal function of cells while improving the proliferation ability in vitro, and to complete the complex mesenchymal epithelialization to achieve tissue remodeling after vivo implantation. Herein, in order to aid HPKs adhesion and proliferation in vitro and promoting wound healing, we developed a three dimensional collagen scaffold with Y-27632 sustainedly released from the nanoplatform, hollow mesoporous organosilica nanoparticles (HMON). The results showed that the porous structure within the TEE supports the implanted HPKs expanding in a three-dimensional mode to jointly construct the tissue-engineered epidermis in vitro and inhibited the mitochondria-mediated cell apoptosis. It was confirmed that the TEEs with suitable degradation rate could maintain drug release after implantation and could accelerate vascularization of wound base and further revealed the involvement of mesenchymal transformation of transplanted HPKs during skin regeneration in a nude mouse model with full-thickness skin resection. In conclusion, our study highlights the great potential of constructing TEE using a nanoparticle platform for the treatment of large-area skin defects.